MODELLING OF THE SUPPLY CHAIN PLANNING FOR THE BUSINESS AND ECONOMIC SECURITY - Vlasov, M. P.; Modenov, A. K.; Harchenko, O. V. (International Journal of Supply Chain Management, 2020)
Abstract? Strategic supply-chain planning that combines aspects of business-strategy formulation with aspects of tactical supply-chain planning can make each far more valuable to the planning effort than either would be alone. The purpose of this article is to assess the economic security of the enterprise in terms of the efficiency of the use of supply chain planning, taking into account the possibility of production and sale of manufactured products. In case of falling demand for products, there are free capacities in the enterprise, which are useful to use to organize the production of additional items. Underutilization of the enterprise leads to higher costs, lower profitability and lower revenues, thus reducing the interest of the owners in the enterprise and thus threatening its existence. The article proposes a system of mathematical models, which allows to effectively use the capacity of the enterprise to increase its profitability due to the self-contained production of additional nomenclature, due to the use of temporarily increasing capacity. As the main hypothesis in the construction of the model, it is assumed that the economic security of the enterprise is determined by the degree of satisfaction of the economic interests of persons interested in the results of its activities. Therefore, it is proposed to consider the economic security of the enterprise from the point of view of effective use of the assets of the enterprise, which creates prerequisites for timely and full fulfilment of mutual obligations by the enterprise on the one hand, and by the owner, personnel, clients, partners, the State on the other. The proposed system of mathematical models implies that the enterprise is oriented towards the production of mass products, the realization of which involves a certain risk. The model assumes that the enterprise produces several types of industrial nomenclature and has the possibility to organize the production of additional nomenclature using available free capacities. The proposed model is intended to assess the feasibility of production, determine the best value for money and thereby increase the profitability of the enterprise. The use of a system of models improves the current activities of the enterprise, the feasibility and effectiveness of the existing innovation policy for the renewal of the production programme. The article provides recommendations for practical use of the model.